Tubular polycrystalline film synthesis post-treatment method, obtained film and application of obtained film

By using the infusion method and rolling coating method on the inner surface of the tubular polycrystalline film, the prepolymer and the crosslinking agent are crosslinked in situ to form a polymer film layer with a crosslinking network structure, and the tubular polycrystalline film is solved. The problem of uneven surface coating significantly improves the separation selectivity and stability of the film.

CN119406255AActive Publication Date: 2025-02-11NANJING TECH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411739064.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to uniformly cover the polymer coating on the inner surface of the tubular polycrystalline film, resulting in a decrease in non-selective defects in the film and a decrease in separation selectivity.

Method used

The prepolymer solution is coated on the inner surface of the tubular polycrystalline film by infusion method, and the prepolymer and the crosslinking agent are crosslinked and cured in situ on the inner surface of the tubular polycrystalline film by rolling coating to form a crosslinking A polymer film layer with network structure.

Benefits of technology

The polymer coating is uniformly covered on the surface of the tubular polycrystalline film, which significantly repairs the film's defects, improves the gas separation selectivity, and enhances the durability and pollution resistance of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406255A_ABST
    Figure CN119406255A_ABST
Patent Text Reader

Abstract

The invention relates to a processing method of a tubular polycrystalline film, the obtained film and application of the film. The present invention relates to a method for treating a tubular polycrystalline film supported by a carrier, the method comprising a step of applying a solution to the inner surface of the tubular polycrystalline film by a perfusion method, the solution comprising a prepolymer and a cross-linking agent, and a step of roll-coating the coated tubular polycrystalline film, in the roll-coating process, the pre-polymer and the cross-linking agent are added to the inner surface of the tubular polycrystalline film, and the cross-linking agent is added to the pre-polymer and the cross-linking agent. The prepolymer and the cross-linking agent are subjected to an in-situ cross-linking reaction, and the in-situ cross-linking temperature is 25-60 DEG C. According to the treatment method, a uniformly covered polymer coating can be obtained on the surface of the tubular polycrystalline film, so that the purpose of remarkably repairing defects of the tubular polycrystalline film is achieved, and the gas separation selectivity of the tubular polycrystalline film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention specifically relates to a method for post-synthesis treatment of a tubular polycrystalline membrane, the obtained membrane and applications thereof. Background Art

[0002] Membrane separation technology has the characteristics of small carbon footprint, environmental friendliness and low investment cost. It is expected to replace / couple cryogenic distillation technology to achieve efficient separation of low-carbon hydrocarbons in the petrochemical industry. At present, a variety of crystal membranes have been reported to be able to effectively carry out mixed gas separation processes. For example, metal organic frameworks (MOFs) have finely designed and functionalized pore structures, high porosity and surface area; zeolite molecular sieves have uniform pore sizes and good chemical and thermal stability, providing solutions for many challenging gas separations (hydrocarbons with the same carbon number, hydrocarbon isomers, etc.).

[0003] From the perspective of industrial application, separation membranes should meet the requirements of high preparation repeatability, high stability, durability and anti-pollution ability while ensuring high separation performance. Polycrystalline membranes supported by carriers, such as ceramic-supported polycrystalline membranes, have the characteristics of high packing density and mechanical strength, and can meet the harsh conditions of industrial applications. However, due to the fragility, symbiosis and preparation repeatability of polycrystalline membranes, non-selective defects of the membrane will inevitably occur, especially when the inner surface curvature of the carrier increases, especially when the carrier is tubular, it will aggravate the further formation of non-selective defects on the membrane surface.

[0004] Therefore, the development of new technologies to repair defects in polycrystalline membranes supported by tubular carriers is crucial to promote the industrial application of membrane separation in the petrochemical industry. The prior art usually focuses on coating modification on polycrystalline membranes supported by flat plates to repair defects in polycrystalline membranes. For example, Chinese patent CN108939958A discloses coating a polymer solution on a flat plate-supported MOF membrane to modify and repair defects, wherein the polymer is silicone rubber, polyether-polyamide copolymer, PTMSP, polyimide or PIM polymer, and the above polymer is a fully cross-linked polymer. Directly coating it is prone to bubbling and shedding of the polymer coating, resulting in reduced separation selectivity of the composite membrane. In addition, the polymer solution has a certain viscosity, and it is usually difficult to form a continuous coating of uniform thickness on the inner surface of the tubular membrane with limited space, and it is difficult to effectively repair the defects of the tubular polycrystalline membrane. Summary of the invention

[0005] The object of the present invention is to provide a method for treating a tubular polycrystalline membrane, which can obtain a uniformly covered polymer coating on the surface of the tubular polycrystalline membrane, thereby achieving the purpose of significantly repairing the defects of the tubular polycrystalline membrane and improving its gas separation selectivity.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for processing a tubular polycrystalline membrane, wherein the tubular polycrystalline membrane is supported by a carrier. The method comprises the steps of coating a solution on the inner surface of the tubular polycrystalline membrane by a perfusion method, wherein the solution comprises a prepolymer and a cross-linking agent, and rolling coating the tubular polycrystalline membrane after the perfusion coating, wherein the prepolymer and the cross-linking agent undergo an in-situ cross-linking reaction, and the rolling coating temperature is 25 to 60°C.

[0008] In the present invention, the perfusion method refers to perfusing the prepolymer solution into the tubular polycrystalline membrane supported by the carrier, allowing the prepolymer solution to spontaneously infiltrate the inner surface of the tubular polycrystalline membrane and gradually penetrate, and after the coating is completed, the excess solution in the tubular polycrystalline membrane is discarded.

[0009] Although the prior art discloses coating a polymer coating on a flat-plate-supported polycrystalline membrane to repair polycrystalline membrane defects, it is difficult to form a uniform polymer film layer on the inner surface of a tubular polycrystalline membrane using conventional coating methods, which easily leads to uneven polymer film layer thickness in different upper and lower regions of the tubular polycrystalline membrane. In addition, in the prior art, a cross-linked polymer is directly coated on the surface of the polycrystalline membrane, which easily causes bubbling and shedding of the coating during membrane testing, making it difficult to effectively repair polycrystalline membrane defects, and the separation selectivity of the composite membrane is greatly reduced under high pressure conditions.

[0010] The present invention first pre-coats a layer of solution including a prepolymer and a cross-linking agent on the surface of a tubular polycrystalline membrane by a perfusion method, and then rolls the membrane. During the roll coating process, the prepolymer and the cross-linking agent are in-situ cross-linked and cured on the inner surface of the tubular polycrystalline membrane, and a polymer membrane layer with a cross-linked network structure is generated on the inner surface of the tubular polycrystalline membrane, thereby obtaining a uniform and continuous polymer coating on the inner surface of the tubular polycrystalline membrane. At the same time, by controlling the temperature of the roll coating, on the one hand, the prepolymer and the cross-linking agent can undergo sufficient cross-linking reaction during the roll coating process, and on the other hand, the temperature is controlled so that part of the solvent in the coating solution slowly evaporates at the relatively low temperature (relative to the boiling point of the solvent), thereby avoiding excessive evaporation of the solvent in the coating during the subsequent drying process due to the high drying temperature, thereby causing pore defects in the polycrystalline membrane coating, which is not conducive to improving the selectivity of the membrane when used for gas separation. The treatment method of the present invention can effectively repair the defects of large-area tubular polycrystalline membranes, and improve their durability, anti-pollution and separation stability under high pressure in practical applications.

[0011] In some embodiments, the prepolymer is selected from one or both of divinyl-terminated polydimethylsiloxane and divinyl-terminated polydimethylsiloxane containing C1-C6 fluoroalkyl groups in the side chain, and the cross-linking agent is a siloxane compound containing two or more silicon-hydrogen bonds. The two vinyl end groups on the prepolymer react with the two or more silicon-hydrogen bonds on the cross-linking agent to form a cross-linked polymer network structure.

[0012] In some embodiments, the C1-C6 fluoroalkyl group is selected from fluoropropyl.

[0013] In some embodiments, the prepolymer is selected from one or both of dihydroxy-terminated polydimethylsiloxane and dihydroxy-terminated polydimethylsiloxane containing C1-C6 fluoroalkyl groups in the side chain, and the crosslinking agent is selected from one or more combinations of tetraethyl orthosilicate, tetramethyl orthosilicate and tetrapropyl orthosilicate. The two hydroxyl end groups on the prepolymer undergo condensation reaction with the silicate group on the crosslinking agent to form a crosslinked polymer network structure.

[0014] In some embodiments, the C1-C6 fluoroalkyl group is selected from fluoropropyl.

[0015] In some embodiments, the solution further comprises a catalyst for catalyzing a cross-linking reaction between the prepolymer and the cross-linking agent. Under the action of the catalyst, the prepolymer and the cross-linking agent are more likely to undergo a cross-linking reaction, and the cross-linking curing rate is faster.

[0016] In some embodiments, the catalyst is selected from a platinum catalyst or an organotin catalyst, the platinum catalyst is used to catalyze the addition reaction of vinyl and silicon-hydrogen bonds, and the organotin catalyst is used to catalyze the condensation reaction of hydroxyl and silicate groups. When the prepolymer is selected from one or both of divinyl-terminated polydimethylsiloxane and divinyl-terminated polydimethylsiloxane containing C1-C6 fluoroalkyl groups in the side chain, and the cross-linking agent is a siloxane compound containing two or more silicon-hydrogen bonds, the catalyst is a platinum catalyst. When the prepolymer is selected from one or both of dihydroxy-terminated polydimethylsiloxane and dihydroxy-terminated polydimethylsiloxane containing C1-C6 fluoroalkyl groups in the side chain, and the cross-linking agent is selected from one or more combinations of tetraethyl orthosilicate, tetramethyl orthosilicate and tetrapropyl orthosilicate, the catalyst is an organotin catalyst, for example, dibutyltin dilaurate.

[0017] In some embodiments, the rolling coating is performed at a rotation speed of 30-180 r / min.

[0018] In some embodiments, the rolling coating time is 1 to 9 hours.

[0019] In some embodiments, the coating time by the perfusion method is 5 to 20 minutes.

[0020] In some embodiments, the mass concentration of the solution is 5% to 30%.

[0021] In some embodiments, the mass ratio of the prepolymer to the cross-linking agent is 5-20:1.

[0022] In some embodiments, the tubular polycrystalline membrane is selected from one or both of a MOF membrane and a zeolite membrane.

[0023] The tubular polycrystalline film of the present invention can be prepared by a secondary growth method or an in-situ synthesis method. The secondary growth method refers to the process of introducing a layer of nanocrystalline seeds on the surface of the carrier in advance by chemical methods such as dipping, spraying or in-situ crystallization, and then immersing the carrier in a reaction solution to obtain a dense polycrystalline film through secondary growth. The in-situ synthesis method refers to a method of immersing the carrier vertically or horizontally in the reaction solution, and causing the polycrystalline material to nucleate, crystallize and finally grow together to form a dense film on the surface of the carrier at a certain temperature.

[0024] In some embodiments, the support is selected from a combination of one or more of a porous alumina ceramic tube, a hollow fiber alumina ceramic tube, and a porous stainless steel sintered tube.

[0025] In some embodiments, the carrier is selected from a combination of one or more of a single-channel tube, a 4-channel tube, a 7-channel tube, a 19-channel tube, and a 61-channel tube.

[0026] In some embodiments, the roll coating is performed on a temperature-controlled roll coating apparatus.

[0027] In some embodiments, the temperature-controlled rolling coating apparatus includes a main body containing a chamber, a plurality of rollers located inside the main body, a motor, a temperature controller, and a transmission belt located inside the main body, the rollers are used to drive the tubular polycrystalline film to roll, the motor drives the rollers to rotate through the transmission belt, and the temperature controller is used to control the temperature inside the main body.

[0028] In some embodiments, the motor is located outside the body.

[0029] In some embodiments, the tubular polycrystalline film is placed between two of the rollers.

[0030] In some embodiments, the number of the rollers is 4-8.

[0031] In some embodiments, the temperature controller is located on an outer wall of the body.

[0032] In some embodiments, the treatment method further comprises a drying step after roll coating.

[0033] In some embodiments, the drying temperature is 60-100°C.

[0034] In some embodiments, the drying time is 6 to 24 hours.

[0035] The present invention also provides a tubular polycrystalline membrane obtained by the above-mentioned tubular polycrystalline membrane treatment method. After the above-mentioned treatment, the defects of the tubular polycrystalline membrane are significantly repaired, the polymer coating on its inner surface is uniform, and the gas separation selectivity of the tubular polycrystalline membrane is significantly improved.

[0036] The present invention also provides the use of the tubular polycrystalline membrane for separation of gases, wherein the gases are selected from one or more combinations of hydrogen, nitrogen, carbon dioxide, methane, ethane, ethylene, propane, and propylene.

[0037] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0038] (1) The inner tube space of the tubular polycrystalline membrane is limited, and the polymer solution usually has a certain viscosity. It is difficult to obtain a uniform polymer coating on the inner surface of the tubular polycrystalline membrane by traditional dipping, spin coating and the like. The present invention first pre-coats a layer of a solution including a prepolymer and a cross-linking agent on the surface of the tubular polycrystalline membrane supported by a carrier by perfusion coating, and then performs roll coating on it. During the rolling coating process, the prepolymer and the cross-linking agent are in situ cross-linked and cured on the inner surface of the tubular polycrystalline membrane, thereby generating a polymer film layer with a cross-linked network structure on the inner surface of the tubular polycrystalline membrane, thereby obtaining a uniform and continuous polymer coating on the inner surface of the tubular polycrystalline membrane, thereby avoiding the uneven thickness distribution caused by the gravity of the polymer solution itself, thereby achieving the purpose of effectively repairing the defects of the polycrystalline membrane.

[0039] (2) The present invention uses a prepolymer and a cross-linking agent for in-situ curing and cross-linking, and cooperates with a rolling coating process, so that the polymer can be evenly covered on the inner surface of a spatially confined tubular polycrystalline membrane and in-situ cross-linked and cured on the surface of the polycrystalline membrane, so that the low molecular weight prepolymer can penetrate into the intercrystalline defects, and then effectively repair the intercrystalline defects through in-situ cross-linking, and strengthen the interfacial bonding between the coating and the membrane layer. At the same time, it avoids the formation of a thick coating due to increased viscosity after the polymer is completely cross-linked, and weak bonding with the body membrane, resulting in bubbling and shedding of the polymer coating.

[0040] (3) By controlling the temperature of the rolling coating, on the one hand, the prepolymer and the cross-linking agent can undergo sufficient cross-linking reaction during the rolling coating process at this temperature, and on the other hand, the temperature is controlled so that part of the solvent in the coating solution evaporates slowly at this relatively low temperature (relative to the boiling point of the solvent), thereby avoiding the subsequent drying process, because the high drying temperature will cause the solvent in the coating to evaporate too quickly, thereby causing pore defects in the polycrystalline membrane coating, which is not conducive to improving the selectivity of the composite membrane when used for gas separation. The treatment method of the present invention can effectively repair the defects of large-area tubular polycrystalline membranes, and improve their durability, anti-pollution properties and separation stability under high pressure in practical applications.

[0041] (4) For low-selectivity tubular polycrystalline membranes dominated by defects, the treatment method of the present invention can effectively fill the non-selective defects generated in the preparation process of the tubular polycrystalline membrane, thereby improving its gas separation performance under normal pressure; and for some tubular polycrystalline membranes dominated by flexible skeleton problems, this method can further restrict their flexible frame structure on the basis of repairing the defects, thereby improving their gas separation performance under high-pressure environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 : The structural schematic diagram of the temperature-controlled rolling coating apparatus for implementing the rolling coating process of the present invention, wherein: 1-roller, 2-motor, 3-transmission belt, 4-temperature controller, 5-main body.

[0043] Figure 2 : Cross-sectional electron micrograph of the tubular polycrystalline film after treatment in Example 1.

[0044] Figure 3 : Cross-sectional electron micrograph of the tubular polycrystalline film after treatment in Comparative Example 1.

[0045] Figure 4 : A diagram showing the relationship between the separation selectivity of the tubular polycrystalline membrane before and after treatment in Example 1 and the increase in pressure, wherein the left figure is before treatment and the right figure is after treatment.

[0046] Figure 5 : A diagram showing the relationship between the separation selectivity of the tubular polycrystalline membrane before and after treatment as the pressure increases in Example 2, wherein the left figure is before treatment and the right figure is after treatment.

[0047] Figure 6 : A diagram showing the relationship between the separation selectivity of the tubular polycrystalline membrane before and after treatment as the pressure increases in Example 3, wherein the left figure is before treatment and the right figure is after treatment.

[0048] Figure 7 : A diagram showing the relationship between the separation selectivity of the tubular polycrystalline membrane before and after treatment as the pressure increases in Example 4, wherein the left figure is before treatment and the right figure is after treatment.

[0049] Figure 8 : A diagram showing the relationship between the separation selectivity of the tubular polycrystalline membrane before and after treatment as the pressure increases in Example 5, wherein the left figure is before treatment and the right figure is after treatment.

[0050] Fig. 9 : A diagram showing the relationship between the separation selectivity of the tubular polycrystalline membrane before and after treatment as the pressure increases in Example 6, wherein the left figure is before treatment and the right figure is after treatment.

[0051] Fig.10: Comparative Example 2 is a graph showing the relationship between the separation selectivity of the tubular polycrystalline membrane before and after treatment as the pressure increases, wherein the left graph is before treatment and the right graph is after treatment.

[0052] Fig.11 : Cross-sectional electron micrograph of the tubular polycrystalline film after treatment in Comparative Example 3. DETAILED DESCRIPTION

[0053] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.

[0054] The rolling coating of the present invention is as follows Figure 1 The temperature-controlled rolling coating apparatus shown in the figure is carried out. The temperature-controlled rolling coating apparatus comprises a main body 5 with a chamber inside, a plurality of rollers 1 located inside the main body 5, a motor 2 located outside the main body 5, a temperature controller 4, and a transmission belt 3 located inside the main body 5. The roller 1 is used to drive the tubular polycrystalline film to roll, the motor 2 drives the roller 1 to rotate through the transmission belt 3, and the temperature controller 4 is used to control the temperature inside the main body 5. There can be 4-8 rollers 1, Figure 1 The rollers 1 shown in FIG. are 4, as shown in FIG. Figure 1 As shown, the temperature controller 4 can be located on the outer wall of the main body 5 for easy operation. The main body 5 is provided with a hole for the transmission belt 3 to pass through, and the transmission belt 3 is sleeved on the motor 2 and the roller 1, and the two adjacent rollers 1 are also connected by the transmission belt 3.

[0055] The rolling coating in the following embodiments is performed using the aforementioned temperature-controlled rolling coating apparatus, and the tubular polycrystalline film is placed between two rollers 1 .

[0056] Example 1

[0057] This embodiment provides a single-channel tubular ZIF-8 polycrystalline membrane and processes it as follows:

[0058] 1) Preparation of single-channel tubular ZIF-8 membrane supported by porous alumina ceramics: A cleaned 13 cm porous alumina ceramic tube was immersed in a seed solution (Zn(NO3)·6H2O: 2-methylimidazole (2-MIM): H2O in a molar ratio of 1:60:1200 and stirred at room temperature for 12 h. After washing with methanol and centrifuging three times, the particles were dispersed in fresh methanol to obtain a seed solution) for 2 min. After completing the seed inoculation procedure, the tube was dried at room temperature. The tube was then placed in a reactor containing a secondary synthesis solution (Zn(NO3)·6H2O: 2-MIM: H2O in a molar ratio of 1:60:6000, and stirred evenly to obtain a secondary synthesis solution) and reacted for 12 h. Finally, the tube was taken out and washed 2 to 3 times with a methanol solution to obtain a single-channel ZIF-8 tubular membrane.

[0059] 2) Membrane treatment: Liquid A (containing vinyl-terminated polydimethylsiloxane PDMS and a platinum catalyst) and liquid B (containing a cross-linking agent with more than two silicon-hydrogen bonds) of the RTV615 two-component silicone rubber compound produced by General Electric were added to an n-heptane solvent at a mass ratio of 10:1, and rapidly stirred for 15 minutes to dissolve to prepare a solution with a mass concentration of 20 wt%. The solution was defoamed by ultrasound for 5 minutes. One end of the tubular membrane was blocked with a rubber stopper, and the prepolymer solution was poured into the tube for coating for 10 minutes. Then the excess solution was poured out, and the tubular membrane was placed on a temperature-controlled rolling coater and rolled for 6 hours. At the same time, the temperature of the temperature-controlled coater was controlled at 40°C, so that the prepolymer and cross-linking agent in the solution were in situ cross-linked and cured on the inner surface of the tubular membrane under the action of the catalyst, and part of the solvent was slowly evaporated. Finally, the single-channel tubular ZIF-8 membrane was dried at 100°C for 24 hours, and a uniform, continuous polymer coating that could effectively repair defects was obtained on the inner surface, and finally a treated tubular polycrystalline membrane was obtained.

[0060] The cross-sectional electron microscope image of the tubular polycrystalline film after the above treatment is as follows: Figure 2 As shown, it can be seen that the polymer coatings in the upper and lower regions of the tubular polycrystalline membrane are very uniform, and the thickness of the polymer coatings in the two regions is substantially the same, which can effectively repair the defects of the membrane.

[0061] The single-channel ZIF-8 tubular membranes obtained in multiple steps 1) and the treated tubular polycrystalline membranes obtained in multiple steps 2) were subjected to the following gas separation performance tests:

[0062] The membranes were placed in the homemade membrane modules respectively, and the propylene / propane separation experiment was carried out: propylene / propane (equimolar feed), mixed gas flow rate 80ml / min, nitrogen as purge gas, nitrogen gas flow rate 240ml / min, transmembrane pressure difference range 1-6bar. The results are as follows: The separation performance of the single-channel ZIF-8 tubular membrane obtained in step 1) is as follows Figure 4 As shown in the left figure, the separation performance of the treated tubular polycrystalline membrane obtained in step 2) is as follows Figure 4 As shown in the right figure, it can be seen that after the treatment of the present invention, the gas separation capabilities of the membrane under normal pressure and high pressure environments are significantly improved, because the treatment method of the present invention repairs the defects of the membrane.

[0063] Example 2

[0064] This embodiment provides a single-channel tubular SSZ-13 zeolite membrane and processes it as follows:

[0065] 1) Preparation of single-channel tubular SSZ-13 zeolite membrane supported by porous alumina ceramic: A layer of seed crystals (Na2O:Al2O3:SiO2:H2O:N,N,N-trimethyl-1-adamantanammonium hydroxide (TMAdaOH) in a molar ratio of 1:2.5:100:4400:20) was coated on the surface of a cleaned 13 cm porous alumina ceramic tube and placed in a reactor at 160°C for 96 h, washed with water, centrifuged three times and dried, and calcined at 600°C. After 6 hours of removing the structure directing agent, the seeds were collected. After completing the seed inoculation procedure, the tubular membrane was dried at room temperature. The tubular membrane was then placed in a reactor filled with a secondary synthesis liquid (the molar ratio of Na2O:Al2O3:SiO2:H2O:TMAdaOH was 1:1:20:1600:10, and the secondary synthesis liquid was obtained after stirring evenly) and reacted for 48 hours. Finally, the membrane was taken out and washed with water for 2 to 3 times, and calcined in an oxygen environment at 400°C for 48 hours to obtain a single-channel SSZ-13 tubular zeolite membrane.

[0066] 2) Membrane treatment: Liquid A (containing vinyl-terminated polydimethylsiloxane PDMS and a platinum catalyst) and liquid B (containing a cross-linking agent with more than two silicon-hydrogen bonds) of the RTV615 two-component silicone rubber compound produced by General Electric were added to an n-heptane solvent at a mass ratio of 10:1, and rapidly stirred for 15 minutes to dissolve to prepare a solution with a mass concentration of 20 wt%. The solution was defoamed by ultrasound for 5 minutes. One end of the tubular membrane was blocked with a rubber stopper, and the prepolymer solution was poured into the tube for coating for 10 minutes. Then the excess solution was poured out, and the tubular membrane was placed on a temperature-controlled rolling coater and rolled for 6 hours. At the same time, the temperature of the temperature-controlled coater was controlled at 40°C, so that the prepolymer and cross-linking agent in the solution were in situ cross-linked and cured on the inner surface of the tubular membrane under the action of the catalyst, and part of the solvent was slowly evaporated. Finally, the single-channel tubular Si-CHA zeolite membrane was dried at 100°C for 24 hours, and a uniform, continuous polymer coating that could effectively repair defects was obtained on the inner surface, and finally a treated tubular polycrystalline membrane was obtained.

[0067] The membranes obtained in multiple steps 1) and the treated tubular polycrystalline membranes obtained in multiple steps 2) were subjected to the following gas separation performance tests:

[0068] The membranes were placed in the self-made membrane modules and the carbon dioxide / methane separation experiment was carried out: carbon dioxide / methane (equimolar feed), mixed gas flow rate 80ml / min, helium as purge gas, helium gas flow rate 240ml / min, transmembrane pressure difference range 1-6bar. The results are as follows: The separation performance of the membrane obtained in step 1) is as follows Figure 5 As shown in the left figure, the separation performance of the treated tubular polycrystalline membrane obtained in step 2) is as follows Figure 5As shown in the right figure, it can be seen that after the treatment of the present invention, the gas separation capabilities of the membrane under normal pressure and high pressure environments are significantly improved, because the treatment method of the present invention repairs the defects of the membrane.

[0069] Example 3

[0070] This embodiment provides a 19-channel tubular SSZ-13 zeolite membrane and processes it as follows:

[0071] 1) Preparation of 19-channel tubular SSZ-13 zeolite membrane supported by porous alumina ceramic: A layer of seed crystals (SiO2:Al2O3:TMAdaOH:NaOH:H2O molar ratio of 1:0.025:0.4:0.2:44) was coated on the surface of a cleaned 6.5 cm porous alumina ceramic tube and placed in a reactor for reaction at 160°C for 96 h, washed with water, centrifuged three times and dried, calcined at 600°C for 6 h to remove the structure directing agent, and then the crystals were collected. After the seed inoculation procedure is completed, the membrane is dried at room temperature, and then the tubular membrane is placed in a reactor filled with a secondary synthesis liquid (Na2O:Al2O3:SiO2:H2O:TMAdaOH with a molar ratio of 1:0.025:0.2:0.2:25, and the secondary synthesis liquid is obtained after stirring evenly) to react for 48 hours, and finally the membrane is taken out and washed with water 2 to 3 times, and the single membrane is calcined in an oxygen environment at 200°C for 48 hours to obtain a 19-channel SSZ-13 tubular zeolite membrane.

[0072] 2) Membrane treatment: Liquid A (containing vinyl-terminated polydimethylsiloxane PDMS and a platinum catalyst) and liquid B (containing a cross-linking agent with more than two silicon-hydrogen bonds) of the RTV615 two-component silicone rubber compound produced by General Electric were added to an n-heptane solvent at a mass ratio of 10:1, and rapidly stirred for 15 minutes to dissolve to prepare a solution with a mass concentration of 20 wt%. The solution was defoamed by ultrasound for 5 minutes. One side of the 19-channel tubular membrane was sealed with plastic wrap, and the prepolymer solution was poured into the tube for coating for 20 minutes. Then the excess solution was poured out, and the tubular membrane was placed on a temperature-controlled rolling coater and rolled for 9 hours. At the same time, the temperature of the temperature-controlled coater was controlled at 40°C, so that the prepolymer and cross-linking agent in the solution were in situ cross-linked and cured on the inner surface of the tubular membrane under the action of the catalyst, and part of the solvent was slowly evaporated. Finally, the membrane was dried in an oven set at 100°C for 48 hours. The inner surface of the 19-channel tubular ZIF-8 membrane obtained a uniform, continuous polymer coating that could effectively repair defects, and finally a treated tubular polycrystalline membrane was obtained.

[0073] The same carbon dioxide / methane separation experiment as in Example 2 was carried out, and the results were as follows: the separation performance of the membrane obtained in step 1) was as follows Figure 6 As shown in the left figure, the separation performance of the treated tubular polycrystalline membrane obtained in step 2) is as follows Figure 6As shown in the right figure, it can be seen that after the treatment of the present invention, the gas separation capabilities of the membrane under normal pressure and high pressure environments are significantly improved, because the treatment method of the present invention repairs the defects of the membrane.

[0074] Example 4

[0075] The method is basically the same as Example 1, except that the RTV615 two-component silicone rubber compound in step 2) is replaced by an RTV107 two-component silicone rubber compound, wherein component A is hydroxyl-terminated polydimethylsiloxane PDMS, component B is a crosslinking agent tetraethyl orthosilicate, and a catalyst dibutyltin dilaurate, and the mass ratio of the three is 100:10:1.

[0076] The propylene / propane gas separation experiment was carried out in the same manner as in Example 1. The results showed that the separation performance of the membrane obtained in step 1) was as follows: Figure 7 As shown in the left figure, the separation performance of the treated tubular polycrystalline membrane obtained in step 2) is as follows Figure 7 As shown in the right figure, it can be seen that after the treatment of the present invention, the gas separation capabilities of the membrane under normal pressure and high pressure environments are significantly improved, because the treatment method of the present invention repairs the defects of the membrane.

[0077] Example 5

[0078] The method is basically the same as Example 1, except that the temperature of the rolling coating in step 2) is replaced from 40°C to 60°C.

[0079] The propylene / propane gas separation experiment was carried out in the same manner as in Example 1. The results showed that the separation performance of the membrane obtained in step 1) was as follows: Figure 8 As shown in the left figure, the separation performance of the treated tubular polycrystalline membrane obtained in step 2) is as follows Figure 8 As shown in the right figure, it can be seen that after the treatment of the present invention, the gas separation capabilities of the membrane under normal pressure and high pressure environments are significantly improved, because the treatment method of the present invention repairs the defects of the membrane.

[0080] Example 6

[0081] The method is basically the same as Example 1, except that the temperature of the rolling coating in step 2) is replaced from 40°C to 25°C.

[0082] The propylene / propane gas separation experiment was carried out in the same manner as in Example 1. The results showed that the separation performance of the membrane obtained in step 1) was as follows: Fig. 9 As shown in the left figure, the separation performance of the treated tubular polycrystalline membrane obtained in step 2) is as follows Fig. 9 As shown in the right figure, it can be seen that after the treatment of the present invention, the gas separation capabilities of the membrane under normal pressure and high pressure environments are significantly improved, because the treatment method of the present invention repairs the defects of the membrane.

[0083] Comparative Example 1

[0084] This comparative example provides a single-channel tubular ZIF-8 polycrystalline membrane, and processes it as follows:

[0085] 1) Same as step 1) in Example 1;

[0086] 2) Membrane treatment: Liquid A (containing vinyl-terminated polydimethylsiloxane PDMS and containing a platinum catalyst) and liquid B (containing a cross-linking agent with more than 2 silicon-hydrogen bonds) in the RTV615 two-component silicone rubber compound produced by General Electric are added to n-heptane solvent in a mass ratio of 10:1, and rapidly stirred for 15 minutes to dissolve, and a solution with a mass concentration of 20wt% is prepared. The solution is defoamed by ultrasound for 5 minutes. One end of the tubular membrane is blocked with a rubber stopper, and the prepolymer solution is perfused into the tube for coating for 10 minutes, then the excess solution is poured out, and the tubular membrane is then placed vertically on filter paper at 40°C for 6 hours, and finally dried in an oven at 100°C for 24 hours to obtain the treated membrane. The cross-sectional electron micrograph of the tubular polycrystalline membrane after the above treatment is as follows: Figure 3 As shown, it can be seen that the polymer coatings in the upper and lower regions of the tubular polycrystalline membrane are uneven, the polymer coating in the upper region is thin, and the polymer coating in the lower region is thick and uneven.

[0087] Comparative Example 2

[0088] The method is basically the same as Example 1, except that the temperature of the rolling coating in step 2) is replaced from 40°C to 70°C.

[0089] The propylene / propane gas separation experiment was carried out in the same manner as in Example 1. The results showed that the separation performance of the membrane obtained in step 1) was as follows: Fig.10 As shown in the left figure, the separation performance of the treated tubular polycrystalline membrane obtained in step 2) is as follows Fig.10 As shown in the figure on the right, it can be seen that when the temperature of the rolling coating is too high, the degree of polymer repair of defects is limited and the degree of improvement in membrane separation performance is very low.

[0090] Comparative Example 3

[0091] The scheme of coating after complete cross-linking is adopted, as follows:

[0092] The method is basically the same as Example 1, except that step 2) is different. Step 2) is as follows:

[0093] Liquid A (containing vinyl-terminated polydimethylsiloxane PDMS and platinum catalyst) and liquid B (containing a cross-linking agent with more than 2 silicon-hydrogen bonds) in the RTV615 two-component silicone rubber compound produced by General Electric were added to the n-heptane solvent at a mass ratio of 10:1, and heated in a water bath at 30°C and stirred for 24 hours to completely cross-link the polymer. One end of the tubular film was blocked with a rubber stopper, and the cross-linked polymer was poured into the tube for coating for 10 minutes, and then the excess solution was poured out, and the tubular film was placed on a temperature-controlled rolling coating instrument, and rolled for 6 hours, while the temperature of the temperature-controlled coating instrument was controlled at 40°C, and part of the solvent was slowly evaporated, and finally dried for 24 hours at an oven temperature set at 100°C, and finally the treated tubular polycrystalline film was obtained.

[0094] The propylene / propane gas separation experiment was carried out in the same manner as in Example 1. During the test, bubbling was found on the membrane surface.

[0095] The coating of the tubular polycrystalline membrane finally obtained is relatively thick and has weak bonding force, resulting in separation of the coating and the membrane layer, and bubbling phenomenon, such as Fig.11 shown.

[0096] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for processing a tubular polycrystalline membrane, wherein the tubular polycrystalline membrane is supported by a carrier, characterized in that: The treatment method comprises the steps of coating a solution on the inner surface of the tubular polycrystalline membrane by a perfusion method, wherein the solution comprises a prepolymer and a cross-linking agent, and rolling-coating the coated tubular polycrystalline membrane, wherein during the rolling coating, the prepolymer and the cross-linking agent undergo an in-situ cross-linking reaction, and the in-situ cross-linking temperature is 25 to 60°C.

2. The method for processing a tubular polycrystalline film according to claim 1, characterized in that: The prepolymer is selected from one or both of bisvinyl-terminated polydimethylsiloxane and bisvinyl-terminated polydimethylsiloxane with C1-C6 fluoroalkyl groups in the side chain, and the crosslinking agent is a siloxane compound containing two or more silicon-hydrogen bonds; or, the prepolymer is selected from one or both of bishydroxy-terminated polydimethylsiloxane and bishydroxy-terminated polydimethylsiloxane with C1-C6 fluoroalkyl groups in the side chain, and the crosslinking agent is selected from one or more combinations of tetraethyl orthosilicate, tetramethyl orthosilicate and tetrapropyl orthosilicate.

3. The method for processing a tubular polycrystalline film according to claim 1, characterized in that: The rolling coating is carried out at a rotation speed of 30-180 r / min; and / or, the rolling coating time is 1-9 hours; and / or, the perfusion coating time is 5-20 minutes.

4. The method for processing a tubular polycrystalline film according to claim 1, characterized in that: The mass concentration of the solution is 5% to 30%; and / or the mass ratio of the prepolymer to the cross-linking agent is 5-20:

1.

5. The method for processing a tubular polycrystalline film according to claim 1, characterized in that: The tubular polycrystalline membrane is selected from one or both of MOF membrane and zeolite membrane.

6. The method for processing a tubular polycrystalline film according to claim 1, characterized in that: The carrier is selected from a combination of one or more of porous alumina ceramic tubes, hollow fiber alumina ceramic tubes, and porous stainless steel sintered tubes; preferably, the carrier is selected from a combination of one or more of single-channel tubes, 4-channel tubes, 7-channel tubes, 19-channel tubes, and 61-channel tubes.

7. The method for processing a tubular polycrystalline film according to claim 1, characterized in that: The rolling coating is carried out on a temperature-controlled rolling coating apparatus; the temperature-controlled rolling coating apparatus includes a main body containing a chamber, a plurality of rollers located inside the main body, a motor, a temperature controller, and a transmission belt located inside the main body, the rollers are used to drive the tubular polycrystalline film to roll, the motor drives the rollers to rotate through the transmission belt, and the temperature controller is used to control the temperature inside the main body; preferably, the number of the rollers is 4-8; the temperature controller is located on the outer wall of the main body.

8. The method for processing a tubular polycrystalline film according to claim 1, characterized in that: The treatment method further comprises a drying step after rolling coating; preferably, the drying temperature is 60 to 100° C. and the drying time is 6 to 24 hours.

9. A tubular polycrystalline film obtained by the method for treating a tubular polycrystalline film according to any one of claims 1 to 8.

10. Use of the tubular polycrystalline membrane according to claim 9, characterized in that: Used for separation of gas, wherein the gas is selected from one or more combinations of hydrogen, nitrogen, carbon dioxide, methane, ethane, ethylene, propane, and propylene.

Citation Information

Patent Citations

  • Method for improving the gas separation performance of supported MOF membrane by utilizing polymer coating

    CN108939958A

  • Preparation method of PIM-1@MOFs / polymer composite pervaporation membrane

    CN110026097A

  • Method for repairing tubular zeolite membrane for reverse osmosis water treatment

    CN110523292A

  • Preparation method of multichannel SSZ-13 molecular sieve membrane

    CN112499642A

  • Film preparation method based on slit extrusion type coating

    CN118022554A